A case of crescentic glomerulonephritis with exacerbation of pre-existing IgA nephropathy after COVID-19 - Karabağ Yılmaz, Esra; Saygılı, Seha; Musayeva, Gülüstan; Gülmez, Rüveyda; Ağbaş, Ayşe; Özlük, Yasemin; Canpolat, Nur (The Turkish Journal of Pediatrics, 2024)
Background. Relapses or new-onset IgA nephropathy (IgAN) have been documented in patients after vaccination against SARS-CoV-2; however, only one adult patient has been reported in whom pre-existing IgAN worsened during coronavirus disease 2019 (COVID-19).Case. We present the first pediatric case with biopsy-proven IgAN and genetically confirmed Alport syndrome, who developed end-stage kidney disease after an exacerbation of IgAN associated with COVID-19. The patient’s basal serum creatinine was 0.7-0.9 mg/dL before infection. He had not been vaccinated against COVID-19. He was admitted to the hospital with edema, hypertension, an elevated serum creatinine of 4.7 mg/dL, and massive proteinuria. Three months before admission, he had been admitted to another hospital with COVID -19 and an elevated serum creatinine (1.9 mg/dL), but no biopsy had been performed at that time. The kidney biopsy revealed IgAN with 50% fibrocellular crescents with sclerosed glomeruli, tubular atrophy, and interstitial fibrosis. His serum creatinine did not decrease even after five administrations of pulse steroids, and hemodialysis was initiated.Conclusion. In conclusion, COVID -19 may pose a high risk for exacerbation of pre-existing glomerular disease. It is therefore necessary to closely monitor the kidney function of patients with underlying glomerulonephritis during and after COVID-19 and consider an early biopsy if serum creatinine does not return to baseline levels. In addition, this case report highlights the clinical importance of the co-occurence of IgAN and Alport syndrome.
Keywords: Alport syndrome; children; crescentic glomerulonephritis; COVID-19; IgA nephropathy